Antioxidant Evaluation and Heavy Metals Accumulation Of Capsicum Annuum L. Cultivars (Bangladesh Journal of Botany, 2021)
Capsicum annuum L. commonly known as chilli provides dietary fibers, minerals and vitamins. In this study, three different chilli cultivars commonly named as Dandi, Ghotki and German were studied for the determination of physico-chemical properties, antioxidant activity and metal content. German showed maximum nutritional components as compared to Ghotki and Dandi such as TA (0.43 %), TDS (1.95 g/l), TSS (1.29 °Brix) and TSC (1108.72 mg/100 g). Dandi showed higher TPC (6286.60 mg/100 g) and TFC (258.88 mg/100 g) with significant antioxidant activity through DPPH (37.27 % inhibition) and RPA (1134.80 mg/100 g). Fe was found in sufficient amount among chilli cultivars and metals accumulation was within the standard safe limits.Bangladesh J. Bot. 50(3): 507-513, 2021 (September)